Giant Aortic Aneurysm in Refractory Behçet’s Disease Shrank with Tocilizumab Treatment: A Case Report - Zi‐Yi Song; Xin Zhi; Jia‐Yi Geng; Xing Sun; Tian Liu; Zhan‐Guo Li (ACR Open Rheumatology)
Behçet disease (BD) is characterized by recurrent oral and genital ulcers, skin lesions, and vascular involvement. Giant aortic aneurysm, a life‐threatening complication of BD, often proves refractory to conventional therapies. Here, we present the case of a 71‐year‐old man with a 40‐year history of BD complicated by a giant aortic aneurysm, which was successfully managed using the interleukin‐6 (IL‐6) receptor antagonist tocilizumab (TCZ). Despite years of tight treatment with high‐dose glucocorticoids and immunosuppressants, there were frequent flares of disease and aortic aneurysm formation. Following the initiation of TCZ therapy, the patient achieved remarkable clinical improvement: the aortic aneurysm diameter decreased significantly from 10.15 × 7.83 cm to 6.22 × 5.12 cm, and disease activity, as measured by the Behçet's Disease Current Activity Form score, dropped from 8 to 1, indicating sustained disease control. This case underscores the potential of IL‐6 inhibition as a transformative therapeutic strategy for refractory BD with severe vascular complications, offering new hope for patients with this challenging condition.